2005
DOI: 10.1124/jpet.105.089086
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Pyrrole-Imidazole Polyamide Inhibits Expression of the Human Transforming Growth Factor-β1 Gene

Abstract: Pyrrole-imidazole (Py-Im) polyamides can bind to the predetermined base pairs in the minor groove of double-helical DNA with high affinity. These synthetic small molecules can interfere with transcription factor-DNA interaction and inhibit or activate the transcription of corresponding genes. In the present study, we designed and synthesized a Py-Im polyamide to target Ϫ545 to Ϫ539 base pairs of human transforming growth factor-␤1 (hTGF-␤1) promoter adjacent to the fat-specific element 2 (FSE2) to inhibit the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
47
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 31 publications
0
47
0
Order By: Relevance
“…The combination of Im/ Py recognizes GC in the DNA double-helix, Py/Py recognizes TA and AT and arrangements of these combinations made it possible to bind to a variety of sequence. Since they can bind DNA with higher affinity and specificity than the usual DNA binding proteins, PIPs designed to recognize the binding Inhibition of MMP-9 using a pyrrole-imidazole polyamide reduces cell invasion in renal cell carcinoma (15)(16)(17)(18). Previously, we reported that PIP targeting for MMP-9 inhibit the migration and invasion of colon cancer cells in vitro and also inhibits their metastasis in vivo (19).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of Im/ Py recognizes GC in the DNA double-helix, Py/Py recognizes TA and AT and arrangements of these combinations made it possible to bind to a variety of sequence. Since they can bind DNA with higher affinity and specificity than the usual DNA binding proteins, PIPs designed to recognize the binding Inhibition of MMP-9 using a pyrrole-imidazole polyamide reduces cell invasion in renal cell carcinoma (15)(16)(17)(18). Previously, we reported that PIP targeting for MMP-9 inhibit the migration and invasion of colon cancer cells in vitro and also inhibits their metastasis in vivo (19).…”
Section: Introductionmentioning
confidence: 99%
“…Binding site specificity is dependent on the side-byside pairing of pyrrole (Py) and imidazole (Im): the Py/Im pair targets the CG base pair, Py/Im recognizes the GC base pair, and Py/Py binds both AT and TA base pairs. [7][8][9] We demonstrated that PI polyamides targeting transforming growth factor-β1 (TGF-β1) potentially and transcriptionally improved progressive renal diseases, [10][11][12] arterial stenosis and hypertrophic scars.13) We also developed PI polyamides targeting lectin-like oxidative low-density lipoprotein (LDL) receptor-1 for atherosclerotic diseases.14) These PI polyamides were designed to bind to the transcription factor binding region in the promoter region of dsDNA and powerfully suppress the transcription of the target genes. It remains to be elucidated whether the pairing rules of PI polyamide for the DNA double helix are also available to bind to double-helical RNA.…”
mentioning
confidence: 99%
“…We developed PI polyamides targeted to TGF-β1 as practical medicines that would transcriptionally inhibit the TGF-β1 gene (21,22). In the current study, to develop a PI polyamide targeted to the TGF-β1 promoter as a new therapeutic medicine for EPS, we examined the effects of our PI polyamide on expression by mesothelial cells of ECM mRNAs in vitro, and we evaluated EPS by histology and high-resolution regional elasticity mapping in rats in vivo.…”
mentioning
confidence: 99%